Forced migration and education - Iryna Kushnir (University of Aberdeen, School of Education, 2020)
This feature provides a brief account of the contemporary context of forced migration globally and the issues around education for refugees who have fled their home countries and live in exile. This discussion is informed by Paulo Freire's ideas of oppression and liberation and suggests that refugees live in the context of oppression, which stems from the forced migration and may continue through education provision in host communities. While the generosity of the hosts in this provision should be recognised, the lack of refugees' agency in this provision is the factor linked to oppression.